APPLICATION OF MODIFIED ATMOSPHERE PACKAGING (MAP) ON FRESH FISH - Putri Wullandari; Diini Fithriani (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Packaging has many functions, e.g. as containment, to protect products from physical damage,and from H2O, O2, and CO2 exposure, as well as to attract the consumers. Based on the technology,packaging can be divided into 3 types i.e. passive packaging, active packaging, and smartpackaging. Modified Atmosphere Packaging (MAP) is the most common active packaging foundin the market. MAP has been used to extend the shelf life of several fish such as raw whiting (codfamily), mackerel, salmon fillet, cod fillet, fresh bluefin tuna fillet, etc. MAP which was combinedwith freeze-chilling has been proved to extend the shelf life of raw whiting, mackerel, and salmonfillet. MAP also increased cod fillet’s shelf life up to 20 days, whiting fillets packed in 100% CO2and stored at 4°C temperature up to 15 days. MAP combined with antioxidant on fresh bluefin tunafillets stored at 3°C for 18 days was able to extend products shelf life from 2 days (control) to 18days, meanwhile 100% N2 in packaging has protective effect on haemoglobin and lipid oxidation.Packaging innovations and ingenuity will continuously develop MAP that is oriented for consumer,enhance the product, environmentally responsive, friendly, and cost effective.